Amerika serikat. Bangsa baru yang pertama. Dalam perspektif sejarah dan kopmparatif - LIPSET, Seymour Martin (Sinar Harapan, 1994)
Amerika serikat . Bangsa baru yang pertama. Dalam perspektif sejarah dan ...